Numerical simulation of the influence of the fluctuations of the biosensor’s parameters on its response - Štikonienė, Olga; Ivanauskas, Feliksas (Lietuvos matematikos rinkinys, 2009)
The mathematical model of the electrochemical glucose biosensor based on the enzymatic conversion of the substrate and the diffusion of the substrate was used. The influence of the fluctuations of the membrane thickness, the diffusion coefficients and pH were modelled and their impact was evaluated at different modes of an action of the biosensor.